Berberine inhibits adipocyte differentiation, proliferation and adiposity through down-regulating galectin-3 - Wang, Can; Wang, Yan; Ma, Shu-Rong; Zuo, Zeng-Yan; Wu, Yan-Bin; Kong, Wei-Jia; Wang, Ai-Ping; Jiang, Jian-Dong (Scientific reports, 2019)
This study is designed to investigate the effects of berberine (BBR) on galectin-3 (Gal-3) and the relationships to its suppressive activities on adipocyte differentiation, proliferation and adiposity. Our results showed that BBR greatly suppressed the differentiation and proliferation of mouse primary preadipocytes isolated from epididymal white adipose tissue (eWAT), during which the expression level of Gal-3 was down-regulated significantly. Overexpression of Gal-3 totally abolished the suppressive activities of BBR on Gal-3 expression, preadipocyte differentiation and proliferation. BBR reduced Gal-3 promoter activity, destabilized its mRNA and inhibited firefly luciferase activity of a recombinant plasmid containing the Gal-3 3′ untranslated region (UTR). Furthermore, BBR up-regulated microRNA (miRNA) let-7d expression and the suppressive activity on Gal-3 3′UTR was abolished by point mutation on the let-7d binding site. In mice fed a high-fat diet (HFD), BBR up-regulated let-7d and down-regulated Gal-3 expression in eWAT; it also suppressed adipocyte differentiation and proliferation and reduced adiposity greatly. In summary, our study proves that BBR inhibits the differentiation and proliferation of adipocytes through down-regulating Gal-3, which is closely associated with its anti-obesity effect. Our results may support the future clinical application of BBR for the treatment of obesity or related diseases.